Simvastatin treatment increases nitrite levels in obese women: Modulation by T-786C polymorphism of eNOS - Andrade, V. L.; Sertório, J. T. C.; Eleuterio, N. M.; Tanus-Santos, J. E.; Fernandes, K. S.; Sandrim, V. C. [UNESP] (Elsevier, 2013)
Objective and Subjects: Evidence indicates an impairment of nitric oxide (NO) in obesity. Statins present pleiotropic effects independently of cholesterol-lowering, including increasing of eNOS expression and antioxidant effects. We evaluated the effects of simvastatin treatment at 45 days on circulating nitrite (NO marker) and TBARS-MDA levels in obese women without comorbidities (hypertension, diabetes and dyslipidemia). Moreover, we verified whether obese women carrying the C variant of T-786C polymorphism located in eNOS may have increased levels of nitrite after treatment compared to TT genotype. Results: After simvastatin treatment, while the plasma nitrite levels increased 42% (P = 0.0008), the TBARS-MDA levels reduced 58% (P = 0.0069). We observed increased levels of nitrite in both groups of genotypes (TT vs. TC + CC); however, rise in C-allele carriers was 60% comparing with 44% in TT. Conclusion: Our results demonstrated a restoration of nitrite levels in obese women treated with simvastatin, which is modulated by T-786C polymorphism. © 2013 Elsevier Inc. All rights reserved.
Keywords: ENOS; Nitrite; Obesity; Polymorphism; Statin